Unlocking Indonesia’s Floating Solar Potential: A PPP Regulatory Review - Tri Setiawan, Muchlis Ahmad; Ahmad Sofwan; Harahap, Dahwin Ferry (Journal of Infrastructure Policy and Management (JIPM), 2025)
Indonesia possesses significant potential for the development of Floating Solar Power Plant, or Floating Photovoltaic (FPV) systems, with an estimated capacity of 14,701.71 MWp. Nevertheless, the actual utilization of FPV remains very low. The Ministry of Public Works (MPW) seeks to optimize the use of multipurpose dams as FPV sources through the Public-Private Partnership (PPP) scheme. According to the data released by the Directorate of Dams and Lakes, Directorate General of Water Resources, 257 out of 259 dams nationwide are considered suitable for FPV development. Despite this potential, the implementation of PPP schemes for FPV projects has encountered stagnation. The preliminary evaluations reveal regulatory misalignment between MPW and PT PLN (Persero), which has resulted in a two-stage procurement process that is inefficient and legally ambiguous. These inefficiencies have led to adverse impacts on the government, private sector entities, and society. This study employs a qualitative approach with a Normative Legal Review Gap Analysis framework. The findings highlight the need for regulatory harmonization among MPW, the Ministry of Energy and Mineral Resources, and PT PLN (Persero). Such harmonization would facilitate the establishment of joint Contracting Agencies, a single-stage procurement process, and greater tariff certainty. The study offers policy recommendations that serve as a reference for cross-sectoral regulatory integration and enhance institutional coordination in the development of FPV infrastructure on MPW dams, thereby contributing to Indonesia’s Net Zero Emissions target by 2060.